2014
DOI: 10.1038/srep05260
|View full text |Cite
|
Sign up to set email alerts
|

Identification of temozolomide resistance factors in glioblastoma via integrative miRNA/mRNA regulatory network analysis

Abstract: Drug resistance is a major issue in the treatment of glioblastoma. Almost all glioblastomas are intrinsically resistant to chemotherapeutic temozolomide (TMZ) or develop resistance during treatment. The interaction networks of microRNAs (miRNAs) and mRNAs likely regulate most biological processes and can be employed to better understand complex processes including drug resistance in cancer. In this study, we examined if integrative miRNA/mRNA network analysis using the web-service tool mirConnX could be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…TMZ is a classical chemotherapy drug for glioma, which is normally used by patients with GBM followed by surgical resection and radiotherapy (24). However, the majority of patients with glioma develop resistance to TMZ during treatment (25). Thus, it was hypothesized that glioma may use or develop 'DNA repairing' and 'toxin pumping-out' strategies to remain resistant.…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is a classical chemotherapy drug for glioma, which is normally used by patients with GBM followed by surgical resection and radiotherapy (24). However, the majority of patients with glioma develop resistance to TMZ during treatment (25). Thus, it was hypothesized that glioma may use or develop 'DNA repairing' and 'toxin pumping-out' strategies to remain resistant.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of BRD2 was confirmed by live cell imaging of YFP-BRD2, which showed that BRD2 accumulates as fast as NBS1 to damaged DNA at laserstripes, but with a shorter retention time at DNA lesions as compared to that of NBS1 ( Fig EV2C). PHF6 was also recently identified as a potential sensitizing factor for drug treatment in resistant glioblastoma [45], which indicates that this protein is important for development and tumorigenesis. Interestingly, another hit from our screen, the transcriptional regulator PHF6 (PHD finger 6), was found to be mutated in Börjeson-Forssman-Lehmann syndrome, which is a rare X-linked genetic disorder characterized by mental retardation, craniopharyngeal abnormalities, and hematological cancers [39][40][41][42][43][44].…”
mentioning
confidence: 98%
“…Some chemotherapy can regulate miRNA to modulate tumor growth, such as integrative miRNA/mRNA regulatory network mediates temozolomide resistance in glioblastoma [73]. Some reports advocate nutritional intervention as part of the “watch-and-wait” approach, because diverse dietary bioactive components, e.g., butyrate, folate, retinoids, curcumin, do exert their biological or clinical effects [74], in part, through modulation of miRNA expression [75].…”
Section: Clinical Relevance and Implicationsmentioning
confidence: 99%